Estudo das propriedades mecânicas e penetração de cloretos em concretos com agregados reciclados de construção com alta substituição de cinza volante - Ortolan, Tiago Luis Possebon (2023)
Currently, the civil construction industry chain in Brazil and in the world are increasingly at the heart of discussion about challenges faced to achieve greenhouse gas (GHG) reduction goals by 2050. The cement production chain produces approximately 8% of the world's GHG emissions. Another point of alert is the generation of millions of tons of urban solid waste from construction and demolition, in Brazil, there were 47 million tons in 2020. Seeking to address these two serious problems, construction and demolition waste (CDW) was applied as recycled aggregate (RA) in this research as a substitute for natural coarse aggregate (NA) in conjunction with the replacement of conventional Portland cement by fly ash (FA). With this, the present work aims to observe the effects of RA and FA on the mechanical properties and durability of concrete, mainly regarding the penetration of chloride ions. For this purpose, 8 mix proportions of concrete were cast, two for each RA replacement level, respectively 25%, 50% and 75%, and two for concrete with AN, four of these were made with conventional CPV-ARI cement and the other four with 40% replacement of cement by fly ash. The concretes were analyzed for their compressive strength, elastic modulus, carbonation and resistance to chloride ion ingress. The results showed that the use of AR harmed the concretes mechanical and durability properties, mainly in the contents of 50% and 75%. The replacement of CV resulted in loss of mechanical strength and increase in carbonation, but about the chloride ions entry, the concretes had similar results to the reference one.